2016
DOI: 10.1002/ajmg.a.37805
|View full text |Cite
|
Sign up to set email alerts
|

A novel MED12 mutation: Evidence for a fourth phenotype

Abstract: Mutations of the MED12 gene have been reported mainly in males with FG (Opitz-Kaveggia), Lujan-Fryns, or X-linked Ohdo syndromes. Recently, a different phenotype characterized by minor anomalies, severe intellectual disability (ID), and absent language was reported in female and male patients belonging to the same family and carrying a frameshift MED12 mutation (c.5898dupC). Here, we report on two brothers and their niece affected by severe and mild ID, respectively, where whole exome sequencing combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…X‐inactivation in previous studies has been inconclusive with little correlation of the affected status in heterozygous females to preferential inactivation of the normal ARX allele (measured in blood) [Marsh, et al., ]. Indeed, skewing of X‐inactivation that is not consistent with disease severity has been reported for other X‐linked genes that were originally thought to affect males but have had affected female cases described, including mutations in genes such as USP9X , MTM1 , SLC9A6 , and MED12 [Prontera, et al., ; Reijnders, et al., ; Savarese, et al., ; Sinajon, et al., ]. This highlights the complexity of X‐linked inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…X‐inactivation in previous studies has been inconclusive with little correlation of the affected status in heterozygous females to preferential inactivation of the normal ARX allele (measured in blood) [Marsh, et al., ]. Indeed, skewing of X‐inactivation that is not consistent with disease severity has been reported for other X‐linked genes that were originally thought to affect males but have had affected female cases described, including mutations in genes such as USP9X , MTM1 , SLC9A6 , and MED12 [Prontera, et al., ; Reijnders, et al., ; Savarese, et al., ; Sinajon, et al., ]. This highlights the complexity of X‐linked inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…A novel variant c.5922G > C was reported in three brothers with severe nonsyndromic ID, mild dysmorphic features, along with their heterozygous mother with a mild phenotype characterized by borderline ID and language delay (Bouazzi et al, 2015). Another novel missense mutation c.2312T > C was detected in two males and one female in a family, with severe and mild ID, respectively, with phenotype that overlap in part with those of the patients reported on c.5898dupC and c.5922G > C. In this family, the affected female had a completely skewed XCI pattern (Prontera et al, 2016). The three mutations (c.5898dupC, c.5922G > T, and c.2312T > C) with non-syndromic XLID shared the similar condition that ID, clinical manifestation were milder in heterozygous females in the family, but were particularly severe in the affected males (severe ID and absent or deficient language).…”
Section: Discussionmentioning
confidence: 65%
“…But common spectrums such as skeletal, gastrointestinal, and genital urinary anomalies in the FGS1 and LS are relatively mild or absent in patients with OSMKB (Verloes et al, 2006;Langley et al, 2015). The clinical phenotypes of NSID include intellectual disability and behavioral disorder (Bouazzi et al, 2015;Prontera et al, 2016). Our patient presented with the clinical features that resembled those associated with both FGS1 and LS: macrocephaly, dysgenesis of the corpus callosum, hypotonia, development delay, long and thin face, hypernasal voice, high nasal root, repaired cleft lip and palate, short philtrum, and hyperextensible digits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This patient exhibited no hallmark of these syndromes and presented with a unique phenotype characterized by severe ID and speech delay, hypotonia and ASD. The literature review suggested a fourth MED12‐related disorder, characterized by severe ID and absent or deficient language skills (Bouazzi, Lesca, Trujillo, Alwasiyah, & Munnich, ; Lesca et al, ; Prontera et al, ). Therefore, patient 16, together with the previously reported carriers of the MED12 mutation, showed distinct features that may provide evidence for a fourth MED12‐related disorder.…”
Section: Discussionmentioning
confidence: 99%